A PSO-Optimized Reciprocal Velocity Obstacles Algorithm for Navigation of Multiple Mobile Robots - Ziyad Allawi; Turki Abdalla (Institute of Advanced Engineering and Science, 2015)
In this paper, a new optimization method for the Reciprocal Velocity Obstacles (RVO) is proposed. It uses the well-known Particle Swarm Optimization (PSO) for navigation control of multiple mobile robots with kinematic constraints. The RVO is used for collision avoidance between the robots, while PSO is used to choose the best path for the robot maneuver to avoid colliding with other robots and to get to its goal faster. This method was applied on 24 mobile robots facing each other. Simulation results have shown that this method outperforms the ordinary RVO when the path is heuristically chosen.